Short silica fiber composites with simultaneous interpenetrating polymer networks constituted by siloxane and phenolic systems. Issue 11 (6th June 2017) - Smitha Alex, Ancy; Rajeev, R.S.; Ranjith, R.; Mohammad, Fazil; Gouri, C.; Sekkar, V.
Abstract : Short silica fiber reinforced simultaneous interpenetrating polymer network (IPN) composites comprising of siloxane and resole phenolic units were synthesized through curing of polymethylsilsesquioxane (PMSQ) and phenolic polymer systems along with short silica fibre. IPNs were formed at various PMSQ/phenolic ratios, while weight percentage of silica short fiber was kept at 60% (by weight). The formation of IPN was confirmed by FTIR, TGA and DMA. The effect of IPN composition on the mechanical, thermal, thermo‐physical and dynamic mechanical properties was investigated. The variation in properties was well correlated with the morphological and phase distribution features of IPN and the interaction of matrix with silica fiber. It was found that phenolic addition improved the properties of PMSQ‐silica composite system substantially and the optimal obtained was with 25% phenolic for most of the properties (compressive and flexural strength, toughness and thermal conductivity) due to the complete miscibility of the resultant IPN and its superior interaction with silica fiber. Tensile strength and impact strength showed increasing trend with phenolic content. However, the char residue got decreased with increase in phenolic content. This study shows that the synergy of PMSQ and PF polymeric systems in the form of IPN is worthwhile to be explored further for various potential applications. POLYM. COMPOS., 39:4010–4019, 2018. © 2017 Society of Plastics Engineers